Family with Peutz–Jeghers syndrome in Indonesia. Issue 5 (12th April 2022) - Parewangi, Muhammad Luthfi; Rusman, Resha Dermawansyah; Akil, Fardah; Daud, Nu'man A S; Bachtiar, Rini; Kusuma, Susanto Hendra; Rifai, Amelia; Tahir, Akiko Syawalidhany; Miskad, Upik; Syarifuddin, Erwin
Abstract: Peutz–Jeghers syndrome (PJS) is a rare autosomal dominant disorder characterised by mucocutaneous pigmentation, gastrointestinal polyps and an increased risk of gastrointestinal and other cancers. We report an Indonesian woman, aged 28, with black spots on her lips who had multiple polyps extending from the stomach to the rectum. Her father and a son also had mucocutaneous lesions but they did not undergo gastrointestinal investigations. All three had mutations in the serine/threonine kinase 11 gene ( STK11 ). Abstract : Black spots on the lips of the patient (left) and the patient's child (right).